2021
DOI: 10.3390/life11060542
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM6’s Role as a Chemoresistance and Prognostic Biomarker for Pancreatic Cancer: A Comparison of CEACAM6’s Diagnostic and Prognostic Capabilities with Those of CA19-9 and CEA

Abstract: Survival rates from pancreatic cancer have remained stagnant for decades due to the heterogenic nature of the disease. This study aimed to find a new advanced biomarker and evaluate its clinical capabilities, thus enabling more individualised pancreatic cancer management. Between 2013 and 2020, 267 patients were included in the study. Surgically collected pancreatic tissue samples were analysed via high-definition mass spectrometry. Carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) was discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Using this approach and verifying the data using individual gene expression data, we found that AGR2, CEACAM6, GNMT, PDIA2, POSTN, RBPJL, and S100P are upregulated in pancreatic tumor tissue as compared to non-tumor tissue from Black and White patients (Fig 1). The protein products from AGR2 [16,[23][24][25], CEAMAN6 [26][27][28], GNMT [29,30], PDIA2 [31,32], POSTN [17,33,34], RBPJL [35,36] and S100P [37][38][39] have been reported as potential diagnostic and prognostic biomarkers for pancreatic cancer or have demonstrated to be involved in either pancreatic cancer, initiation, migration, invasion, metastasis, or chemoresistance. This report provides additional evidence to support that these genes are specifically upregulated in pancreatic tumor tissue as compared to non-tumor tissue and their products could potentially serve as differentiating biomarkers in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach and verifying the data using individual gene expression data, we found that AGR2, CEACAM6, GNMT, PDIA2, POSTN, RBPJL, and S100P are upregulated in pancreatic tumor tissue as compared to non-tumor tissue from Black and White patients (Fig 1). The protein products from AGR2 [16,[23][24][25], CEAMAN6 [26][27][28], GNMT [29,30], PDIA2 [31,32], POSTN [17,33,34], RBPJL [35,36] and S100P [37][38][39] have been reported as potential diagnostic and prognostic biomarkers for pancreatic cancer or have demonstrated to be involved in either pancreatic cancer, initiation, migration, invasion, metastasis, or chemoresistance. This report provides additional evidence to support that these genes are specifically upregulated in pancreatic tumor tissue as compared to non-tumor tissue and their products could potentially serve as differentiating biomarkers in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29]61 In addition, it could be used as a prognostic biomarker and some studies have evaluated the prognostic value of CEACAM6 serum levels in patients with cancer. [65][66][67] However, our study aimed to explore the prognostic role of CEACAM6 in human cancers, rather than in blood. With the potential role of CEACAM6 as immune checkpoint inhibitor in tumors, we focused this evaluation only on primary cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CEACAM6 overexpression is generally associated with worse OS and DFS in a variety of solid tumors, 18 and serum CEACAM6 has been reported as a potential biomarker in pancreatic adenocarcinoma and plasma cell disorders. 19 , 20 , 21 In addition, Cao et al. 22 evaluated differentially expressed genes including CEACAM6 in peripheral blood exosomes as potential biomarkers for lung cancer; although the study was not quantitative, CEACAM6 exosome expression was higher in lung adenocarcinoma than in squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%